Studies on Ostrich (Struthio Camelus) - Review - Brassó, Dóra Lili; Béri, Béla; Komlósi, István (Acta Agraria Debreceniensis, 2020)
Ostrich has been reared in Hungary for decades, but we have limited information on this species. The aim of this review was to provide a concise description of the ostrich (Struthio camelus) based on international studies. We were to investigate some of the most relevant parameters, such as egg, meat and skin production. In this critical review we managed to sum up the most significant features and productivity parameters of ostrich and effecting factors. So as to make an accurate description of the species we have to know its morphological, behavioural and physiological characteristics. Ostrich is a very special bird with special nutritional and environmental requirements. Ostrich products, regarding egg, meat and skin are considered luxury products not only in Hungary but also abroad. Though egg has a significant nutritional value, it is mainly used for hatching chicks. In Europe we can expect roughly 40–50 eggs from a hen yearly. Ostrich has a lean meat with high protein and low fat and sodium content, moreover it is rich in minerals and polyunsaturated fatty acids. Having these advantageous qualities, ostrich meat should be part of our healthy diet. Skin production is not important in our country, but there is a special demand for high quality ostrich leather globally. In the future our aim is to conduct a research on some of the parameters. As low production rate and embryo mortality is a great deal of problem in ostrich industry, we need to investigate the incubation environment. There is an apparent disagreement among researchers on optimal slaughter age. This is also an area for further investigation. The value of skin and effecting factors on our climate as well as adaptability of the species are also worth for further investigation together with the nutrition what differs from other ostrich breeding countries. Nowadays, there is a great emphasis placed on animal welfare too.